PEMETAAN MINIMARKET DI KOTA PADANG (JURNAL SPASIAL, 2015)
This study aims to (1) Know the conditions minimarket in Padang, (a) Size minimarket (b) Number of employees minimarket and (2) Determine the distribution pattern minimarket in Padang. This paper research is a descriptive quantitative research. The population in this study were all minimarket in Padang totaling 142 minimarket. With data collection techniques directly into the field. Anailisis spatial data is done by a technique that is the nearest neighbor analysis and descriptive analysis with the calculation of percentages. The results showed that (1) Spread minimarket in the city of Padang, where there are 11 districts in the city of Padang there is one sub-district that does not have the minimarket, Bungus Teluk Kabung sackclo districts. Then it is also known that the category minimarket broad based with most major categories are in the Eastern District of Padang as much as 9 minimarket or 42.86%. While the minimarket by category of employees with most major categories in the District that is as much as 6 minimarket or 60%. (2) Distribution minimartket in Padang is not random pattern, but the pattern is clusters (cluster).Key Words: mapping, minimarket, Average Nearest Neighbor Summary